The Moderating Role of Incarcerated Mothers’ Psychosocial Functioning on the Association Between Maternal Sensitivity and Their Co-Residing Toddlers’ Attachment - İşcanoğlu, Zülal (Criminal justice and behavior, 2022)
The role of incarcerated mothers’ caregiving quality on their co-residing children’s development may not be fully understood without considering mothers’ psychosocial functioning. The current study aims to investigate the moderating role of incarcerated mothers’ psychosocial functioning (i.e., relationship with their outside children’s caregivers, psychological symptoms, and social support) on the associations between maternal sensitivity and their co-residing children’s attachment. The study sample consisted of 68 mothers and their 12- to 43-month-old co-residing children. Maternal sensitivity and child’s attachment were assessed based on a semi-structured mother–child interaction observation. Mothers reported their psychosocial functioning indicators that were determined based on the common distress factors that these mothers experience. Findings suggest that for the mothers who have the lowest relationship quality with their outside children’s caregivers, maternal sensitivity negatively predicts children’s disorganized attachment. Moreover, maternal sensitivity predicted children’s secure attachment positively and anxious attachment negatively only when maternal psychological symptoms were higher.